PROJECT-BASED LEARNING FOR SUSTAINABLE TOURISM: PROTOTYPING A SOLAR-ELECTRIC BOAT IN A POLYTECHNIC SETTING - I Gede Para Atmaja; Mauren Langie; Ventje Lumentut; Ventje Ferdy Aror (EDUCATIONE, 2026)
Mangrove tourism areas are vital ecosystems that function not only as natural attractions but also as coastal buffers supporting biodiversity and environmental balance. However, tourism activities predominantly rely on fossil-fuel boats that cause air and water pollution, noise, and ecosystem disruption. This research aims to design a concept of an electric boat integrated with a photovoltaic (PV) system as an environmentally friendly transportation solution for mangrove tourism. The study applied a Research and Development (R&D) approach, including literature review, user needs assessment, energy requirement analysis, and detailed engineering design. The results show that the designed boat measures 5 meters in length, 1.8 meters in width, with a draft of 0.6 meters and total height of 1.25 meters. The electrical demand was calculated at 826 W with an operational capacity of 3142 Wh. To meet this demand, four 250 Wp solar panels, a solar charge controller rated at 26.04 A, and a single LiFePO4 battery of 48 V/100 Ah were required. The integration of PV systems demonstrated sufficient energy supply for operation under coastal solar exposure. The design significantly reduces fossil fuel dependence, lowers carbon emissions, minimizes noise, and enhances tourist experiences. This concept contributes to the development of sustainable ecotourism practices in coastal mangrove ecosystems. Future research is recommended to test prototype performance in real operational settings and optimize system efficiency across varying weather conditions.